Analisis Pengalaman Konsumen di Pantai Purus Muaro Lasak Padang - vera, okta; Manvi, Kurnia Illahi; Saladin, khairani (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
The purpose of this study is to examine tourism experience at Pantai Purus Muaro Lasak Padang tourist destination. This research is of a descriptive quantitative nature, utilizing causal associative technique, with a total representative sample of 100 individuals. The population in this study consists of tourists vacationing at Pantai Purus Muaro Lasak Padang tourist destination. The sampling technique employed is purposive sampling using specific criteria. The types of data are primary and secondary. The research instrument is a questionnaire (survey) created using a Likert scale that has been validated and tested for reliability. From the conducted research, it is found that the analysis of tourism experience at Pantai Purus Muaro Lasak Padang falls into the category of moderate with a percentage of 69%. Furthermore, results are obtained based on the following indicators: 1) Comfort is categorized as moderate with a percentage of 70%, 2) Educational aspect is categorized as moderate with a percentage of 72%, 3) Hedonic aspect is categorized as moderate with a percentage of 75%, 4) Novelty aspect is categorized as moderate with a percentage of 55%, 5) Safety aspect is categorized as moderate with a percentage of 73%, 6) Beauty aspect is categorized as moderate with a percentage of 77%.